CircRNA screening and ceRNA network construction for milk fat metabolism in dairy cows - Feng, Xiaofang; Cai, Zhengyun; Mu, Tong; Yu, Baojun; Wang, Ying; Ma, Ruoshuang; Liu, Jiaming; Wang, Chuanchuan; Zhang, Juan; Gu, Yaling (Frontiers in Veterinary Science, 2022)
Background: Milk fat is one of the main reference elements for evaluating milk quality and is a primary objective trait for dairy cattle breeding. In recent years, circRNAs have played crucial roles in many biological activities. However, the function and expression profiles of circRNAs in milk fat synthesis in cows are unknown to a great extent. This study used RNA-seq to analyze the genome-wide expression of circRNAs transcripts in Holstein cows' bovine mammary epithelial cells (BMECs) with extreme differences in milk fat percentage. Functional enrichment analysis and weighted gene co-expression network analysis (WGCNA) identified the critical candidate differential circRNAs associated with milk fat metabolism and constructed a lipid metabolism-related ceRNAs interactive regulatory network. Results:309 circRNAs were significantly differentially expressed in high milk fat percentage cows compared to low milk fat percentage cows, of which 150 circRNAs were significantly upregulated and 159 circRNAs were significantly downregulated.Enrichment analysis (GO, KEGG) determined four differential circRNAs(circ_0001122, circ_0007367, circ_0018269, circ_0015179) that potentially regulate milk fat metabolism. The regulatory networks circ_0001122_miR-12043-_LIPG, circ_0007367_miR-331-3p_CIDEA/PML, and circ_0018269_miR-11989_RORC/HPX are potential networks to explore the mechanism of milk lipid regulation.Subsequently, 1773 circRNAs were divided into 18 modules by WGCNA, where the pink module with milk fat percentage significantly negatively correlated(r=-0.85, P=0.007), and this module contained 11 core circRNAs (|MM|≥0.9, |GS|≥0.6), of which six circRNAs belonged to the differential (circ_0010571, circ_0007797, circ_0002746, circ_0003052, circ_0004319, circ_0012840). Constructing ceRNAs regulatory network of six circRNAs, and the protein interaction network of target genes was analyzed using both cytoHubba and MCODE algorithms in Cytoscape to obtain hub genes and core genes is a total of seven (GNB1, GNG2, PLCB1, PLCG1, ATP6V0C, NDUFS4, and PIGH). These genes play critical roles in milk fat metabolism as essential target genes by functional enrichment analysis, and they constitute the ceRNAs most likely to be involved in milk fat metabolism. Conclusion: These results reveal the possible role of circRNAs in milk fat metabolism in dairy cows. Several important circRNAs and ceRNAs affecting milk fat synthesis were identified, providing a new way to understand the complex biology of milk fat synthesis and providing a new research idea.